Integrasi Seni Karawitan ke dalam Kurikulum Pendidikan Seni - Jufri, Jufri; Halim, Mohamad; Alfalah, Alfalah; Zulfahmi, Muhammad; Martis, Martis (Aksara: Jurnal Bahasa dan Sastra, 2024)
Traditional arts education, such as Karawitan, plays an important role in building cultural identity and social skills among students amidst the forces of globalization. Karawitan, as traditional Indonesian music, teaches moral values such as togetherness, mutual cooperation, and collaboration, which support the formation of the younger generation's character. However, the integration of Karawitan into the education curriculum faces several challenges, including limited facilities, insufficient teacher competence, and the perception that traditional arts are less relevant to modern education. This study uses a qualitative approach with a literature review method, examining 50 relevant sources, consisting of 30 journal articles, 10 books, and 10 research reports related to arts education and Karawitan. The data were analyzed using thematic analysis techniques to identify the benefits, challenges, and strategies for implementing Karawitan in education. The results indicate that Karawitan education can increase students' appreciation of local culture and provide an authentic learning experience. For Karawitan to be taught optimally, support from the government and related institutions is necessary, including the provision of resources, teacher training, and relevant teaching materials. The novelty of this study lies in its more comprehensive understanding of practical ways to integrate Karawitan into the education curriculum and highlights the educational values inherent in traditional arts. With proper integration, Karawitan can become an integral part of education, strengthening students' cultural identity and preparing them to face challenges in the globalized world.Keywords: arts education, karawitan, cultural identity, social skills, curriculum integration